An evaluation of intravenous antifungal medications in patients in a paediatric hospital - Thangavelu Rajan, Remya (Curtin University, 2008)
Objective: To retrospectively evaluate intravenous antifungal medications in paediatric patients in a public hospital for children.Method: Data relevant to the antifungal prescription were collected for all the patients <18 years of age who had been prescribed IV antifungal therapy. All paediatric patients prescribed intravenous antifungal treatment for one year (July 2006 to 30th June 2007) at PMH were evaluated retrospectively. The data collected were evaluated against the Australian Therapeutic Guidelines: Antibiotic Version 13 and hospital in house guidelines for IV antifungal therapy from the microbiology department at the hospital.Results: There were 59 patients included in the study and the most frequently diagnosed disease was leukemia. Of the total 59 patients, liposomal amphotericin B (L-AmB) was prescribed for 47 patients, conventional amphotericin B (C-AmB) for four patients, caspofungin for two patients and voriconazole for one patient. Five patients received combination antifungals. The dose of C-AmB was 1 mg/kg/day. Voriconazole dose of 5 mg/kg/day was given for a period of four days for one patient. Nine patients included in this study were neonates and they were prescribed L-AmB, C-AmB and a combination of Voriconazole and L-AmB. 34 patients out of 47 were prescribed 3mg/kg/day of L-AmB and the highest L-AmB dose prescribed was 5 mg/kg/day and the lowest dose was 1 mg/kg/day. The median number of days for L-AmB treatment was found to be 11 days and the maximum was 51 days. Additionally 6% of patients who received L-AmB had oral fluconazole recommended r five days after cessation of L-AmB. It was found that 27% of patients had a low potassium level and a significantly higher proportion of patients had abnormal alanine aminotransferase and 11(18.6%) of the 59 patients had abnormal serum creatinine levels. It was found that the mean temperature decreased to 37.0°C from a 38.3°C from commencement to the cessation of the IV antifungal treatment. The longest duration of antifungal treatment in this study period was L-AmB prescribed for a period of 102 days.The estimated treatment cost for the longest treatment in this study was found to be AUD 34,222 if prepared in the pharmacy (CIVAS) and AUD 43,784 if prepared in the ward setting. Estimated total treatment cost for a four year old patient with a bodyweight of 21 kg on L-AmB for a period of 21 days was found to be AUD 7,803 when prepared in Pharmacy (CIVAS) and AUD 12,029 for Ward reconstitution.Conclusion: The data from this study indicated a satisfactory quality of IV antifungal treatment; however the remaining requirements for appropriate use required additional education. This study found that L-AmB was the antifungal agent of choice. Considerable savings could be made for pharmacy reconstituted IV antifungals by CIVAS over a ward setting where wastage occurs from unused antibiotic vials. At present the understanding of newer antifungal agents in children is limited. In future children should be included in the studies of new antifungal drugs and combination therapy and stratify the results by age, given the potential differences in pharmacokinetics, pharmacodynamics, efficacy and safety and cost.